2018
DOI: 10.1002/bsl.2344
|View full text |Cite
|
Sign up to set email alerts
|

Insanity findings and evaluation practices: A state‐wide review of court‐ordered reports

Abstract: Evaluations of legal sanity are some of the most complex and consequential mental health evaluations that forensic clinicians perform for the courts. Thus, there is strong reason to monitor the wide-scale process and conclusions of sanity evaluations. In this study, we review 1,111 court-ordered sanity evaluation reports submitted by 74 evaluators in Virginia from the first year after the state initiated an oversight system that allowed for such comprehensive review. Overall, the base rate of insanity findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
3
19
1
1
Order By: Relevance
“…This finding echoes the concern identified by Gardner et al. (2018) that few evaluators clearly explained the nexus between psychiatric symptoms and the criteria for insanity, identifying this as an area in clear need of improvement.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding echoes the concern identified by Gardner et al. (2018) that few evaluators clearly explained the nexus between psychiatric symptoms and the criteria for insanity, identifying this as an area in clear need of improvement.…”
Section: Discussionsupporting
confidence: 83%
“…The present study also addressed one of the gaps identified by Gardner et al. (2018) by including an examination of cases through disposition of the charge(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results shed further light on the wide-scale practice of CST evaluation in one state, particularly with respect to the characteristics of evaluation reports, rates of competency findings, and evaluator differences in competence opinions. Similar to Virginia sanity evaluations conducted during the same time frame (see Gardner, Murrie, & Torres, 2018), most CST reports were submitted by evaluators in private practice (66.9% of CST reports; 80.9% of sanity reports), rarely used psychological testing (5.4% of CST reports; 2.0% of sanity reports), 13 and usually provided an "ultimate-issue" opinion (67.7% of CST reports; 75.8% of sanity reports).…”
Section: Discussionmentioning
confidence: 97%
“…Insanity evaluations are among the most complex and controversial mental health assessments that psychiatrists and psychologists perform 1,2 . A forensic evaluator is expected to perform a retrospective evaluation of the defendant’s state of mind at the time of crime, to ascertain the presence of a mental disease or defect and to further verify the existence of a possible relationship between that state of mind and the criminal behavior.…”
Section: Introductionmentioning
confidence: 99%